The Administration Of Nebraska Public Schools: Present Perceptions and Future Needs - Barbara L. Brock; Debra L. Ponec; Vincent Hamman; Lisa Nelson; Lori Goff (Educational Considerations, 1996)
The next generation of children will live in a world that promises to be substantially different than ours.